2015
DOI: 10.1021/acsbiomaterials.5b00139
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Magnitude of Antibody Responses through Biomaterial Stereochemistry

Abstract: D-Amino acid analogs of peptides and proteins are attractive for applications in biotechnology and medicine due to their reduced proteolytic sensitivity. Here, we report that self-assembling peptide nanofibers composed of D-amino acids act as immune adjuvants, and investigate their ability to induce antibody responses in comparison to their L-amino acid counterparts. The model antigenic peptide OVA (chicken egg ovalbumin aa 323−339) from chicken egg ovalbumin, known to elicit antibody responses in mice, was li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 51 publications
1
34
1
Order By: Relevance
“… See also catalytically active amyloids and enantioselective self‐aggregation of peptides to form nanofibers . …”
mentioning
confidence: 99%
“… See also catalytically active amyloids and enantioselective self‐aggregation of peptides to form nanofibers . …”
mentioning
confidence: 99%
“…Several studies have focused directly on the role of chemical functionality presented on surfaces to decipher how immue response is altered . For instance, peptides synthesized with either an L or D stereochemistry have been linked to a model antigen (ovalbumin, OVA) and used to vaccinate mice .…”
Section: Understanding Intrinsic Immunogenicity Of Biomaterials Delivementioning
confidence: 99%
“…Several studies have focused directly on the role of chemical functionality presented on surfaces to decipher how immue response is altered . For instance, peptides synthesized with either an L or D stereochemistry have been linked to a model antigen (ovalbumin, OVA) and used to vaccinate mice . The D stereochemistry, which is less susceptible to enzymatic degradation, led to stronger antibody responses and prolonged antigen presentation compared to the L stereotype .…”
Section: Understanding Intrinsic Immunogenicity Of Biomaterials Delivementioning
confidence: 99%
“…A very recent work, by Yang et al, showed that D-peptide based nanofibers/hydrogel serve as the carrier of antigens for cancer therapy [118], further demonstrating the potentials of this molecular platform based on D-peptides. Considering the advantages of D-peptides, it is likely that future exploration will lead to more applications of D-peptides [119]. …”
Section: D-amino Acid-containing Supramolecular Nanofibers For Drumentioning
confidence: 99%